Combined effects of Tectonics and Glacial Isostatic Adjustment on intraplate deformation in Central and Northern Europe: applications to Geodetic Baseline Analysis - A.M. Marotta; R. Sabadini; J. M. Mitrovica; G. Milne (Journal of Geophysical Research: Solid Earth, 2004)
We use a suite of spherical, thin sheet, finite element model calculations to investigate the pattern of horizontal tectonic deformation within Europe. The calculations incorporate the effects of Africa-Eurasia convergence, Atlantic Ridge push forces, and changes in the lithospheric strength of the East European and Mediterranean subdomains. These predictions are compared to the deformation computed for the same region using a spherically symmetric, self-gravitating, viscoelastic Earth model of glacial isostatic adjustment. The radial viscosity profile and ice history input into the GIA model are taken from a model that ‘‘best fits’’ three-dimensional crustal velocities estimated from the BIFROST Fennoscandian GPS network. The comparison of the tectonic and GIA signals includes predictions of both crustal velocity maps and baseline length changes associated with sites within the permanent ITRF2000 and BIFROST GPS networks. Our baseline analysis includes reference sites in northern and central Europe that are representative of sites at the center, edge, and periphery of the GIA-induced deformation. Baseline length change predictions associated with all three reference sites are significantly impacted by both tectonic and GIA effects, albeit with distinct geometric sensitivities. In this regard, several of our tectonic models yield baseline rates from Vaas, Onsala, and Potsdam to sites below 55_N which are consistent with observed trends. We find that a best fit to the ITRF2000 data set is obtained by simultaneously considering the effects of GIA plus tectonics, where the latter is modeled with a relatively weak Mediterranean subdomain. In this case, the tectonic model contributes to the observed shortening between Onsala/ Potsdam and sites to the south, without corrupting the extension observed for baselines extending from these reference sites and sites to the north; this extension is well reconciled by the GIA process alone.